2017
DOI: 10.14260/jemds/2017/419
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Foetal Outcome in Pregnancies With Borderline Amniotic Fluid Index in a Study in a Tertiary Care Hospital

Abstract: BACKGROUNDAmniotic fluid volume significantly affects the perinatal outcome, hence necessitates its measurement. Many methods are practised worldwide with every method having both advantage and limitations. Sonographic measurements help in assessing amniotic fluid volume antenatally and in intrapartum period as it is non-invasive and easy to use. Also, it is comparable with invasive methods. MATERIALS AND METHODSStudy was conducted in Mahatma Gandhi Memorial Government Hospital, attached to KAP Viswanatham Gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Studies have already proven that the nature and volume of amniotic fluid significantly affects the perinatal outcome. 21 Nature of the amniotic fluid is a predictor of fetal tolerance during labour, and its alterations is associated with an increased risk of abnormal heart rhythms and meconium fluid. Phelan et al studied amniotic fluid index during pregnancy and concluded that its usefulness in the evaluation of fetal monitoring throughout pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have already proven that the nature and volume of amniotic fluid significantly affects the perinatal outcome. 21 Nature of the amniotic fluid is a predictor of fetal tolerance during labour, and its alterations is associated with an increased risk of abnormal heart rhythms and meconium fluid. Phelan et al studied amniotic fluid index during pregnancy and concluded that its usefulness in the evaluation of fetal monitoring throughout pregnancy.…”
Section: Discussionmentioning
confidence: 99%